Model Analisis Jalur Penggangguran terhadap Tingginya Kriminalitas Mengakibatkan Meningkatnya kemiskinan - Sri Wulandari; Dwi Junia Lestari; Elvina Damayanti (Mandalika Mathematics and Educations Journal, 2025)
The Path Analysis Model is a type of research model used to determine relationships both directly and indirectly. The aim of this research is to look at the analysis of the relationship between unemployment and poverty through crime, both directly and indirectly. This research method is linear regression analysis using SPSS software. The results of this research show that: 1) unemployment leads to high levels of criminality in Lampung Province 2) unemployment results in high levels of poverty in Lampung Province 3) poverty does not lead to high levels of criminality in Lampung Province 4) unemployment increases criminality as seen from high levels of poverty in Lampung Province.